A influência do medo no flow - Rossetti, Rafael Diogo (2022)
In this study, we seek to understand the influence of Fear and its aspects on the feeling of flow that can be observed in horror games, enhancing immersion and seeking understanding of the motivators that make players feel attracted to this kind of game, for that, there were the survey of the state of the art existing and already launched references in the universe of games that collaborate for such understanding, then we made a study of all the existing theories that help the game designer in his choices during the game design stage and for finally, we understand the influence and correlation of the types of fears and how they act in the human subconscious and influencing the motivations of the decision process as well as the techniques used and their results related to the environment and film industry. During this study discover a gap of what is currently in the theory of flow and its strands, bringing applicability to the game development, that way, presenting a look to this technic that provides aid to developers to keep players in the flow, supporting Game-Design professionals in decisions and reflections about the insertion of mechanism we named “Micro-Flow”. The implementation of these elements seeks to prevent the player from accessing the “Boring Zone” or at least, seeks to rescue them as fast as possible in case players access it, mitigating the possibility of the awakening of tedious fillings and anxiety about gameplay. In that way, this study is characterized as Applied research, since its goal was to generate a product aimed at solving specific problems through knowledge generated for practical application in a specific context. Finally, we developed a game called Opus Castle that absorbs all the understanding obtained in this study and demonstrates the real application of the theories observed in a final product that was duly documented through GDD and its respective secondary documents that supported the entire trajectory of the game's creation. from the basic design to its completion, made available in full in the annexes of this document